FARMERS AND HERDERS CONFLICT: THE CASE OF OMALA LOCAL GOVERNMENT AREA - Fidelis Achoba; Mercy Ura Abraham (International Studies Journal)
The study analyzed the farmers and herder conflict and its impact on Omala Local Government Area. The Local Government was under the siege of the farmer and herder crisis for a long time. As a result lives and properties worth millions of naira were lost. Using primary and secondary sources, the study examined the situation in Omala Local Government Area of Kogi State and found its impact to be economic, social and physical. The study recommended among other things that the crisis would be averted if the government can secure appropriate ranches for the herders to graze their cattle.